Brain region-specific microglial and astrocytic activation in response to systemic lipopolysaccharides exposure - Brandi, Edoardo; Torres-Garcia, Laura; Svanbergsson, Alexander; Haikal, Caroline; Liu, Di; Li, Wen; Li, Jia-Yi (Frontiers in Aging Neuroscience, 2022)
Microglia cells are the macrophage population within the central nervous system, which acts as the first line of the immune defense. These cells present a high level of heterogeneity among different brain regions regarding morphology, cell density, transcriptomes, and expression of different inflammatory mediators. This region-specific heterogeneity may lead to different neuroinflammatory responses, influencing the regional involvement in several neurodegenerative diseases. In this study, we aimed to evaluate microglial response in 16 brain regions. We compared different aspects of the microglial response, such as the extension of their morphological changes, sensitivity, and ability to convert an acute inflammatory response to a chronic one. Then, we investigated the synaptic alterations followed by acute and chronic inflammation in substantia nigra. Moreover, we estimated the effect of partial ablation of fractalkine CX3C receptor 1 (CX3CR1) on microglial response. In the end, we briefly investigated astrocytic heterogeneity and activation. To evaluate microglial response in different brain regions and under the same stimulus, we induced a systemic inflammatory reaction through a single intraperitoneal (i.p.) injection of lipopolysaccharides (LPS). We performed our study using C57BL6 and CX3CR1+/GFP mice to investigate microglial response in different regions and the impact of CX3CR1 partial ablation. We conducted a topographic study quantifying microglia alterations in 16 brain regions through immunohistochemical examination and computational image analysis. Assessing Iba1-immunopositive profiles and the density of the microglia cells, we have observed significant differences in region-specific responses of microglia populations in all parameters considered. Our results underline the peculiar microglial inflammation in the substantia nigra pars reticulata (SNpr). Here and in concomitance with the acute inflammatory response, we observed a transient decrease of dopaminergic dendrites and an alteration of the striato-nigral projections. Additionally, we found a significant decrease in microglia response and the absence of chronic inflammation in CX3CR1+/GFP mice compared to the wild-type ones, suggesting the CX3C axis as a possible pharmacological target against neuroinflammation induced by an increase of systemic tumor necrosis factor-alpha (TNFα) or/and LPS. Finally, we investigated astrocytic heterogeneity in this model. We observed different distribution and morphology of GFAP-positive astrocytes, a heterogeneous response under inflammatory conditions, and a decrease in their activation in CX3CR1 partially ablated mice compared with C57BL6 mice. Altogether, our data confirm that microglia and astrocytes heterogeneity lead to a region-specific inflammatory response in presence of a systemic TNFα or/and LPS treatment.